(untitled) (Journal of Parents and Teachers, 2014)
Teaching card of the film called Wall-e directed by Andrew Stanton, about environment. From activities before watching the film, from the analysis of many of its sequences and from activities of experience, reflection and action, the author has a bearing on values as respect and care of environment, sustainability and also the possible consequences of not doing it.